Comparison of two extraction methods for the determination of organolead compounds using sodium tetrapropylborate as derivatization reagent - Xu Zhang (Elsevier, 2021)
Two extraction methods of accelerate solvent extraction (ASE) and supercritical fluid extraction (SFE) were used to the extraction of trimethyl lead (TML) and triethyl lead (TEL), which were detected by gas chromatographer coupled with mass spectrometry. Sodium tetrapropylborate, as the derivatization reagent, was applied for the detection of gas chromatography. The recovery rate of ASE were about 88.2% (TML) and 86.4% (TEL) with 15 min consuming. The recovery rate of SFE were about 93.7% (TML) and 94.1% (TEL) with 40 min consuming. Two extraction methods of ASE and SFE were optimized, which were also analyzed in recovery, repeatability, accuracy, limit of detection (LOD) and other aspect. Both ASE and SFE exhibited rational recovery efficiency. The established methods were also applied to the real soil samples. SFE had better extraction effect according to time consumption, recovery rate, LOD and accuracy. However, ASE had more advantages in automated extraction, which could be applied to the pretreatment of large amounts of samples.